EFFECT OF WELDING CURRENT ON MECHANICAL PROPERTIES AND MICROSTRUCTURE OF ALUMINIUM AA1135 ALLOYS BY GAS TUNGSTEN ARC WELDING (GTAW) - Suherman, Suherman; Abdullah, Ilmi; Suprianto; Darma, Surya; Hendri Budi Kurniyanto (Talenta Publisher, 2023)
Aluminium alloys have a wide range of applications in the defence and aerospace industry, including for the manufacture of fuel tanks. The welding Current and type of filler metal significantly affect the microstructure formed and the mechanical strength of metal joints. This study aimed to determine the effect of the kind of filler metal (ER5356 filler metal) and welding current (140 amperes, 160 amperes, and 180 amperes) on the mechanical properties and microstructural of aluminium alloys AA1135 by the GTAW welding process. The results showed that the dendrite size increased with increasing welding current. Furthermore, the micro-hardness of the weld metal shows a decreasing trend with increasing welding current. The maximum tensile strength was obtained at a current power of 160 amperes, and all specimens failed at HAZ. The fracture surface of tensile test observations using SEM showed brittle fracture for Er5356 filler metal specimens, while on the fracture surface of the base metal tensile test specimens, it was observed to show ductile fracture. Welding with a current strength of 180 amperes has met the standard acceptance criteria because no cracks were found on the face bend or the root bend specimen